Lessons in Sustainable Development from Bangladesh and India - Mehta, Simi (Comparative Studies of Sustainable Development in Asia, 2018)
This Palgrave Pivot looks through social, economic, institutional, and environmental lenses to examine sustainable development in India and Bangladesh. The effects of climate change make this comparative study particularly pertinent, as rising sea levels and severe weather events will lead to displacement and migration, exacerbating existing issues. India and Bangladesh share similar cultural and socioeconomic backgrounds and, as a result, face similar challenges: rapid population growth, widespread poverty, food insecurity, and gender inequality. Developing a sustainable future will require policymakers to consider all of these elements in their efforts to create human security.